The Place of English in an Expanding Europe - Sutton, Peter (Armenian Folia Anglistika, 2006)
The article highlights the present state of English and predicts its future in the context of an expanding Europe. The current rate of the development of English is conditioned by the EU activity which being a multi-national, multi-cultural and multi-language body still gives preference to only a handful of languages, especially English. The article specifies the EU actions and initiatives which aim to facilitate the communication-related challenges of the citizens and help the latter use the language properly. The article contains considerable information about the current stage of the development of English in certain EU countries which, in the long run, give the author a chance to predict the spread of the “globalized” English throughout the world.